Unveiling the Consequences of Parliamentary Thresholds on the Quality and Quantity of Political Representation in Multi-Party Systems - Manggalou, Singgih; Jannatul, Ferdous (CV. Era Digital Nusantara, 2024)
Abstract: Implementing Parliamentary Thresholds in Indonesia's multi-party system has significant implications for political dynamics. Parliamentary Thresholds aim to control political party fragmentation and ensure political stability, yet they may also limit the space for inclusive political participation. Purpose: This study aims to analyze the consequences of implementing the Parliamentary Threshold on the quality and quantity of political representation in a multi-party system. Design/Methodology/Approach: This study employs a qualitative descriptive approach to explore the impact of the Parliamentary Threshold on the political dynamics in Indonesia, analyzing data and information from various primary and secondary sources. Findings: The Parliamentary Threshold can reinforce the dominance of major parties, diminish the representation of small and minority parties, and influence overall political participation. Regular evaluations and flexibility in adjusting the Parliamentary Threshold are crucial to balancing political stability and pluralistic representation. Originality/value: This study contributes to understanding the consequences of the Parliamentary Threshold on political representation in the context of multi-party systems, emphasizing adaptability's importance in maintaining the political system's relevance in dynamic democracies.